Neuroprotective effects of GLP-1 class drugs in Parkinson’s disease - Lv, Dongliang; Feng, Peng; Guan, Xueying; Liu, Zhaona; Li, Dongfang; Xue, Cunshui; Bai, Bo; Hölscher, Christian (Frontiers in Neurology, 2024)
Parkinson’s disease (PD) is a chronic, progressive neurological disorder primarily affecting motor control, clinically characterized by resting tremor, bradykinesia, rigidity, and other symptoms that significantly diminish the quality of life. Currently, available treatments only alleviate symptoms without halting or delaying disease progression. There is a significant association between PD and type 2 diabetes mellitus (T2DM), possibly due to shared pathological mechanisms such as insulin resistance, chronic inflammation, and mitochondrial dysfunction. PD is caused by a deficiency of dopamine, a neurotransmitter in the brain that plays a critical role in the control of movement. Glucose metabolism and energy metabolism disorders also play an important role in the pathogenesis of PD. This review investigates the neuroprotective mechanisms of glucagon-like peptide-1 (GLP-1) and its receptor agonists, offering novel insights into potential therapeutic strategies for PD. GLP-1 class drugs, primarily used in diabetes management, show promise in addressing PD’s underlying pathophysiological mechanisms, including energy metabolism and neuroprotection. These drugs can cross the blood–brain barrier, improve insulin resistance, stabilize mitochondrial function, and enhance neuronal survival and function. Additionally, they exhibit significant anti-inflammatory and antioxidative stress effects, which are crucial in neurodegenerative diseases like PD. Research indicates that GLP-1 receptor agonists could improve both motor and cognitive symptoms in PD patients, marking a potential breakthrough in PD treatment and prevention. Further exploration of GLP-1’s molecular mechanisms in PD could provide new preventive and therapeutic approaches, especially for PD patients with concurrent T2DM. By targeting both metabolic and neurodegenerative pathways, GLP-1 receptor agonists represent a multifaceted approach to PD treatment, offering hope for better disease management and improved patient outcomes.